Relevansi Konsep Niat Belajar dalam Kitab Ta’lim Al-Muta’allim terhadap Pendidikan di Era Modern - Niswatun Toyyibah (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Modern education tends to be pragmatic and material-oriented, neglecting the spiritual and moral dimensions. This study aims to examine the application of the concept of the adab (intention to learn) in the book Ta'lim Al-Muta'allim by Sheikh Burhanuddin Az-Zarnuji in the context of modern education. The method used is literature research with a qualitative approach, through descriptive-analytical analysis of the book Ta'lim Al-Muta'allim, books, and related scientific publications. The results show that the concept of intention to learn according to Az-Zarnuji serves as a spiritual, moral, and motivational foundation for seeking knowledge. A sincere intention oriented towards pleasing Allah, eliminating ignorance, and providing benefits can shape the character of students who are disciplined, responsible, and virtuous. In modern education, this concept remains relevant because it can strengthen intrinsic motivation, balance intellectual and character aspects, and provide solutions to spiritual crises. Thus, the integration of the adab (intention to learn) in modern educational practices is crucial for realizing a holistic and character-based education system.